UNA VISIÓN SINGULAR DE LA SOCIEDAD CIVIL Y SUS RELACIONES CON EL ESTADO. EL CASO DE LA ORGANIZACIÓN GRITO DE MALVINAS (BARRIO LAS MALVINAS, CIUDAD DE ROSARIO, ARGENTINA) - Vitola, Verónica Andrea (Tempo da Ciência, 2000)
Over the last decades, the notion of Civil Society has gained a great importance throughout Latin America. International financial institutions, political discourses and the media present Civil Society as one of the principal collaborator in the difficult task of lessen poverty, control the governments and public politics and even take part in the politics formulation. Besides, Civil Society Organizations appear as a place of social participation, representation and democracy. This article tries to introduce another vision of the relationship between Civil Society and State, analyzing the genesis and development of a social organization of Rosario City, Argentina. This vision is particular for two considerations. In the first place, it expects to contribute to another point of view about the relationship between State and Civil Society Organizations; and in the second place it aims to do it by studying a particular case, observing the ideas that other authors have developed in a theoretical way.